2021
DOI: 10.15184/aqy.2021.114
|View full text |Cite
|
Sign up to set email alerts
|

A method for space archaeology research: the International Space Station Archaeological Project

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…As noted by Lynott (1997) We argue here that this stewardship should extend onto other parts of our solar system, and therefore the guiding principle of preservation and stewardship of space heritage should represent the fundamental principle of planetary geoarchaeology. One example of how NASA scientists and archaeologists are currently collaborating to ensure this goal is the International Space Station Archaeological Project (ISSAP) (Walsh, 2012;Walsh & Gorman, 2021). ISSAP represents the first large-scale contemporary archaeology project in space, and has begun a experiments studying the relationship between patterns of material culture and human behavior on the ISS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted by Lynott (1997) We argue here that this stewardship should extend onto other parts of our solar system, and therefore the guiding principle of preservation and stewardship of space heritage should represent the fundamental principle of planetary geoarchaeology. One example of how NASA scientists and archaeologists are currently collaborating to ensure this goal is the International Space Station Archaeological Project (ISSAP) (Walsh, 2012;Walsh & Gorman, 2021). ISSAP represents the first large-scale contemporary archaeology project in space, and has begun a experiments studying the relationship between patterns of material culture and human behavior on the ISS.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, space archaeologists have drawn attention to the need to consider the preservation of space heritage in various Earth‐orbital positions (Clemens, 2009; Gorman, 2005b, 2009d), interplanetary space (Darrin, 2015; Sample, 2009), the ISS (Ali et al, 2022; Walsh & Gorman, 2021), and on Earth (Westwood et al, 2017). Planetary geoarchaeology is dedicated to studying space heritage on extraterrestrial surfaces and extends the applications of space archaeology by increasing our understanding of the past and future under two key principles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial testing using the Flickr photo set showed that manual tagging of people, places, and items could take hours per photo [4]. At the same time, our approach was validated by a pilot study of items displayed on the aft wall of the Russian Zvezda module [6,7].…”
Section: Methodsmentioning
confidence: 99%
“…For this study, we have been collecting occupation data and analyzing it for significant patterns [4]. Here, we report results from Phase 1 of this work, using the metadata from thousands of historic photographs as evidence, together with a list of crew members and their genders, nationalities, and agency affiliations.…”
Section: Datamentioning
confidence: 99%